2017
DOI: 10.1097/gox.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Sciatic Neuropathy after an Autologous Breast Reconstruction in a Massive Weight Loss Patient

Abstract: Summary:Perioperative compression neuropathy is a known potential complication of prolonged surgical procedures. Sciatic postoperative neuropathy has rarely been reported. We present a 34-year-old woman who underwent right breast reconstruction with supercharged (venous anastomosis) transverse rectus abdominis flap and developed bilateral sciatic compression neuropathy. Her history was remarkable for sleeve gastrectomy 2 years earlier resulting in 105 pound weight loss 1 year before breast reconstruction. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Although favor has largely changed to prefer muscle sparing abdominal based perforator flaps, a unique case report was found describing bilateral sciatic neuropathy after a unilateral pedicled, supercharged TRAM flap in a patient with a history of MWL 16 . The 34-year-old patient was in the supine position for 8 hours on standard padding and was then transitioned to a semirecumbent position for 2 additional hours 16 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although favor has largely changed to prefer muscle sparing abdominal based perforator flaps, a unique case report was found describing bilateral sciatic neuropathy after a unilateral pedicled, supercharged TRAM flap in a patient with a history of MWL 16 . The 34-year-old patient was in the supine position for 8 hours on standard padding and was then transitioned to a semirecumbent position for 2 additional hours 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Although favor has largely changed to prefer muscle sparing abdominal based perforator flaps, a unique case report was found describing bilateral sciatic neuropathy after a unilateral pedicled, supercharged TRAM flap in a patient with a history of MWL 16 . The 34-year-old patient was in the supine position for 8 hours on standard padding and was then transitioned to a semirecumbent position for 2 additional hours 16 . Postoperatively, the patient experienced bilateral motor and sensory loss from knees distally, with no abnormalities revealed on electrolyte panel, magnetic resonance imaging of the spine, electromyography, or nerve conduction study 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported on sciatic nerve palsy occurring after breast surgery or body contouring surgery (24,25). This phenomenon may be the "piriformis syndrome", which is a form of sciatica caused by compression of the sciatic nerve by the piriformis muscle (26).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported on sciatic nerve palsy occurring after breast surgery or body contouring surgery. 24 25 This phenomenon may be the “piriformis syndrome,” which is a form of sciatica caused by compression of the sciatic nerve by the piriformis muscle. 26 Of the sciatic nerves, 90% has traditional anatomy with an undivided sciatic nerve emerging below the piriformis muscle in a cadaveric study.…”
Section: Discussionmentioning
confidence: 99%